Bridging Analytical Models and Cfd: Advancing Ammonia Spill Dispersion Predictions - Filippo De Rosa; Pablo Giacopinelli; Felicia Tan; Alexandre Lebas; Christophe Mabilat (Chemical Engineering Transactions)
The dynamics of pool spreading, evaporation, dissolution and dispersion of refrigerated ammonia spills are highly complex, with no readily available models capable of accounting for all relevant thermochemical properties, and their interactions with varying terrains and environmental conditions. To address this gap, this study presents a novel modelling approach to predict accurately ammonia behaviour during accidental releases. The methodology integrates an analytical model for pool spreading and evaporation (on both land and water), advanced Computational Fluid Dynamics (CFD) simulations for the ammonia dispersion in air, and the coupling of analytical and CFD models to ensure accurate predictions. This novel analytical-CFD coupling approach enhances the accuracy in predicting dispersion patterns while maintaining practical computational demands, thereby providing valuable insights for industrial safety planning and risk mitigation.